2012
DOI: 10.1111/j.1540-4560.2012.01733.x
|View full text |Cite
|
Sign up to set email alerts
|

White Privilege Awareness and Efficacy to Reduce Racial Inequality Improve White Americans’ Attitudes Toward African Americans

Abstract: Two experiments examined effects of heightened awareness of white privilege (illegitimate advantages held by White Americans) and efficacy to reduce racial inequality on White American college students’ attitudes toward African Americans and White Americans. Efficacy to reduce inequality was either measured (Experiment 1) or manipulated (Experiment 2), and heightened white privilege awareness (WPA) was either manipulated (Experiment 1) or held constant (Experiment 2). All participants, except control participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 27 publications
8
71
0
1
Order By: Relevance
“…Thus, system-blame leads to system-change (Jones, 2006). Negative and dispositional attributions toward the least privileged could also be improved as a function of the most privileged participants believing that they could be effective in combating a particular manifestation of economic inequality (Stewart et al, 2012). In this line, diversity training exercises following the ones developed to reduce racial prejudice could involve increasing high-SES participants' awareness of their advantages and the social beliefs and structure maintaining that advantage (e.g., Stewart, La Duke, Bracht, Sweet, & Gamarel, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, system-blame leads to system-change (Jones, 2006). Negative and dispositional attributions toward the least privileged could also be improved as a function of the most privileged participants believing that they could be effective in combating a particular manifestation of economic inequality (Stewart et al, 2012). In this line, diversity training exercises following the ones developed to reduce racial prejudice could involve increasing high-SES participants' awareness of their advantages and the social beliefs and structure maintaining that advantage (e.g., Stewart, La Duke, Bracht, Sweet, & Gamarel, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, justification of inequality negatively relates to attitudes toward low-income individuals and redistribution (Cozzarelli, Wilkinson, & Tagler, 1989;Dion, 2010). In this line, previous research has shown that people made aware of their illegitimate privileges are willing to reduce inequality (Stewart, Latu, Branscombe, Phillips, & Denney, 2012). Complementing this work on justification and awareness, the present research aims to investigate the role of legitimizing ideologies in relation to the perceptions of inequality and attitudes toward resource redistribution.…”
Section: Introductionmentioning
confidence: 91%
“…However, identification of factors that influence collective action on behalf of disadvantaged outgroups, a distinct construct with different antecedents than collective action on behalf of one's own group, has only recently begun to be a focus of research attention (Beaton & Deveau, 2005;Doosje, Branscombe, Spears, & Manstead, 1998;Iyer & Ryan, 2009;Iyer, Schmader, & Lickel, 2007;Leach, Iyer, & Pedersen, 2006;Mallett et al, 2008;Stewart, Latu, Branscombe, Phillips, & Denney, 2012).…”
Section: Downloaded By [The Agamentioning
confidence: 99%
“…The unit presented information on Australia's history of race relations and migration, and Indigenous perspectives, with the aim of highlighting that issues of diversity need to be understood as products of social, cultural, and historical processes. Several resources were useful in framing the pedagogy for the unit, including whiteness studies (Green, Sonn, & Matsebula, ; Stewart, Latu, Branscombe, Phillips, & Denney, ) and cultural safety frameworks (Downing & Kowal, ; Downing, Kowal, & Paradies, ). Whiteness or White privilege is conceptualised as the invisible (or taken‐for‐granted) power and advantages, which are available to culturally dominant group members at an institutional and social level (Case, ).…”
Section: Intercultural Unit Of Study Frameworkmentioning
confidence: 99%
“…Whiteness studies also highlight the covert discrimination experienced by minoritised group members as a result of the taken‐for‐granted racial privilege experienced by majority group members (Green et al., ; Stewart et al., ). It has been argued that inclusion of whiteness studies is a necessary complementary approach to anti‐racism pedagogy (Green et al., ; Stewart et al., ). That is, increasing the awareness of majority group members about the “illegitimate advantages that they hold in society” has resulted in lower levels of prejudice attitudes among university students (Stewart et al., , p. 12).…”
Section: Intercultural Unit Of Study Frameworkmentioning
confidence: 99%